Designing to Leverage Presence in VR Rhythm Games - Robert Dongas; Kazjon Grace (Multimodal Technologies and Interaction, 2023)
Rhythm games are known for their engaging gameplay and have gained renewed popularity with the adoption of virtual reality (VR) technology. While VR rhythm games have achieved commercial success, there is a lack of research on how and why they are engaging, and the connection between that engagement and immersion or presence. This study aims to understand how the design of two popular VR rhythm games, Beat Saber and Ragnarock, leverages presence to immerse players. Through a mixed-methods approach, utilising the Multimodal Presence Scale and a thematic analysis of open-ended questions, we discovered four mentalities which characterise user experiences: action, game, story and musical. We discuss how these mentalities can mediate presence and immersion, suggesting considerations for how designers can leverage this mapping for similar or related games.